2009
DOI: 10.1007/s11104-009-0007-0
|View full text |Cite
|
Sign up to set email alerts
|

Responses of two rice cultivars differing in seedling-stage nitrogen use efficiency to growth under low-nitrogen conditions

Abstract: Demand for low-input nitrogen sustainable rice is increasing to meet the need for environmentally friendly agriculture and thus development of rice with high nitrogen use efficiency (NUE) is a major objective. Hence, understanding how rice responds to growth under low-nitrogen conditions is essential to devise new ways of manipulating genes to improve rice NUE. In this study, using two rice varieties with different seedling-stage NUE obtained from previous field experiments, we investigated the physiological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 41 publications
1
59
0
Order By: Relevance
“…Plants were harvested (including senescing leaves) then dried in an oven for 30 min at 105°C, then at 70°C to a constant weight and weighed. N concentration was determined using the Kjeldahl method (Shi et al, 2010;Han et al, 2015b); 0.2 g of dried samples were digested with H 2 SO 4 -H 2 O 2 in a 100-mL Kjeldahl digestion flask, after which N concentration was determined using a Foss Auto Analyzer Unit (Kjeldahl 8400).…”
Section: Acc Treatmentmentioning
confidence: 99%
“…Plants were harvested (including senescing leaves) then dried in an oven for 30 min at 105°C, then at 70°C to a constant weight and weighed. N concentration was determined using the Kjeldahl method (Shi et al, 2010;Han et al, 2015b); 0.2 g of dried samples were digested with H 2 SO 4 -H 2 O 2 in a 100-mL Kjeldahl digestion flask, after which N concentration was determined using a Foss Auto Analyzer Unit (Kjeldahl 8400).…”
Section: Acc Treatmentmentioning
confidence: 99%
“…2B). This increased expression at a higher dose may be associated with high levels of available nutrients in the environment because GS2 is the main glutathione synthetase isoform found in the leaves, and its overexpression is associated with maintaining photosynthetic capacity, photorespiration in plants and nitrogen assimilation (Shi et al, 2010). Furthermore, we did not observe differences upon comparing the doses with equal proportions of competing plants; however, the red rice monoculture showed its highest level of expression at the highest dose of nitrogen examined.…”
Section: Expression Of Genes Responsible For Nitrogen Assimilationmentioning
confidence: 53%
“…1). The AMT proteins in plants are located in the plasma membrane, which suggests that they play a role in ammonium uptake in plant cells (Shi et al, 2010). When we supplied nitrogen to plants at the appropriate dose (120 kg ha -1 ), expression of AMT mRNA increased in red rice plants.…”
Section: Expression Of Genes Responsible For Nitrogen Assimilationmentioning
confidence: 96%
“…This confirmed that the response of root to salt stress was more sensitive than that of leaf. Plant root was the primary Shi et al 2009). Glutamine synthetase (GS) primarily exists as two isozymes with different subcellular localisations: GS1 in the cytosol and GS2 in chloroplasts/plastids (Kusano et al 2011).…”
Section: Resultsmentioning
confidence: 99%